2016
DOI: 10.1016/j.ntt.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Tert-butylhydroquinone compromises survival in murine experimental stroke

Abstract: tert-butylhydroquinone (tBHQ), an Nrf2 signaling pathway inducer that is widely used as a food additive in the U.S., prevents oxidative stress-induced cytotoxicity in neurons. This study assesses the effects of tBHQ on ischemic stroke outcomes in mice. We measured infarct size, neurological deficits, and brain volume after tBHQ treatments in murine permanent middle cerebral artery occlusion (pMCAO) model in vivo. Further, we evaluated the regulation of tBHQ on mitochondrial function in cerebrovascular endothel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…If the cell density is below 8 × 10 3 cells per well, the basal OCR is too low to be analyzed (Figure 2 and Figure 3); if the cell density is above 32 × 10 3 cells per well, the cells do not respond to oligomycin or FCCP treatments (Figure 2 and Figure 3). The optimal cell density for this cell line in our experimental model is 16 × 10 3 cells per well, which demonstrates replicable results and sensitivity to stimuli 7 and treatments 10,14 . If a 24-well bioanalyzer is used, new titrations of the cell density would be required for the assay.…”
Section: Critical Steps Within the Protocolsupporting
confidence: 62%
See 1 more Smart Citation
“…If the cell density is below 8 × 10 3 cells per well, the basal OCR is too low to be analyzed (Figure 2 and Figure 3); if the cell density is above 32 × 10 3 cells per well, the cells do not respond to oligomycin or FCCP treatments (Figure 2 and Figure 3). The optimal cell density for this cell line in our experimental model is 16 × 10 3 cells per well, which demonstrates replicable results and sensitivity to stimuli 7 and treatments 10,14 . If a 24-well bioanalyzer is used, new titrations of the cell density would be required for the assay.…”
Section: Critical Steps Within the Protocolsupporting
confidence: 62%
“…We have demonstrated that insults to CVE cells following exposure to lipopolysaccharide (LPS) impair mitochondrial function in CVE cells and worsen stroke outcomes 7 . Tert-butylhydroquinone (tBHQ) increases stroke mortality by interfering with oxidative phosphorylation in CVE cells 10 . Therefore, the quantitative model of bioenergetic function in CVE cells not only pilots a series of mechanism-related studies for central nervous system (CNS) diseases, but also provides a breakthrough in drug screening of therapeutics targeting mitochondrial function in vascular biology.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that Nrf2 upregulation by tBHQ significantly reduced the expression of cytoplasmic thioredoxin interacting protein, nod-like receptor protein 3 (NLRP3) inflammasome, and downstream factors caspase-1, IL-1β, and IL-18, all of which contribute to the Nrf2-mediated neuroprotection against ischemic outcomes after tMCAO (Hou et al, 2018 ). Interestingly, there is a contradictory report that tBHQ-exacerbated stroke damage (Sun et al, 2016 ), revealed by increased post-stroke mortality and worsened outcomes after pMCAO.…”
Section: Nrf2 Targeted Intervention In Ischemic Stroke—advancements Fmentioning
confidence: 99%
“…Continuous tBHQ treatment markedly decreased and ameliorated proteinuria in type 1 diabetes mice [20]. Also, intra-cerebroventricular administration with tBHQ significantly reduced size of infraction and neurological disfunction was improved [21,22]. Moreover, tBHQ protected hepatocytes from saturated fatty acids induced cells death by enhancing autophagy [14].…”
Section: Discussionmentioning
confidence: 98%